HUBUNGAN DUKUNGAN SOSIAL DENGAN PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS PONDOKGEDE BEKASI - Pertiwi, Nur Fitri Ayu (Poltekkes Kemenkes Maluku, 2023)
Fulfillment of nutrition for newborn babies is very dependent on breast milk (ASI). Increasing the quantity and quality of breast milk needs to be a priority in fulfilling the nutrition of newborn babies. Breast milk production is closely related to the conditions of social support around the mother. Social support is important to support the success of exclusive breastfeeding. This research aims to determine the relationship between social support and exclusive breastfeeding in the Pondok Gede Bekasi Community Health Center area. This research design uses cross sectional. The sample used was 129 mothers with toddlers aged 6-24 months. The sampling technique was accidental sampling using a questionnaire as a research instrument. The research results were analyzed using the Chi-Square test with a result of p<0.05. The research results show that there is a relationship between social support and exclusive breastfeeding. It is hoped that all parties will provide full support for the success of exclusive breastfeeding.